Biodegradation of Crude Oil by Nitrate-Reducing, Sulfate-Reducing, and Methanogenic Microbial Communities under High-Pressure Conditions - Lu Wang; Yong Nie; Xinglong Chen; Jinbo Xu; Zemin Ji; Wenfeng Song; Xiaofang Wei; Xinmin Song; Xiao-Lei Wu (Microorganisms, 2024)
Carbon capture, utilization, and storage (CCUS) is an important component in many national net-zero strategies, and ensuring that CO2 can be safely and economically stored in geological systems is critical. Recent discoveries have shown that microbial processes (e.g., methanogenesis) can modify fluid composition and fluid dynamics within the storage reservoir. Oil reservoirs are under high pressure, but the influence of pressure on the petroleum microbial community has been previously overlooked. To better understand microbial community dynamics in deep oil reservoirs, we designed an experiment to examine the effect of high pressure (12 megapascals [MPa], 60 °C) on nitrate-reducing, sulfate-reducing, and methanogenic enrichment cultures. Cultures were exposed to these conditions for 90 d and compared with a control exposed to atmospheric pressure (0.1 MPa, 60 °C). The degradation characteristic oil compounds were confirmed by thin-layer analysis of oil SARA (saturates, aromatics, resins, and asphaltenes) family component rods. We found that the asphaltene component in crude oil was biodegraded under high pressure, but the concentration of asphaltenes increased under atmospheric pressure. Gas chromatography analyses of saturates showed that short-chain saturates (C8–C12) were biodegraded under high and atmospheric pressure, especially in the methanogenic enrichment culture under high pressure (the ratio of change was −81%), resulting in an increased relative abundance of medium- and long-chain saturates. In the nitrate-reducing and sulfate-reducing enrichment cultures, long-chain saturates (C22–C32) were biodegraded in cultures exposed to high-pressure and anaerobic conditions, with a ratio of change of −8.0% and −2.3%, respectively. However, the relative proportion of long-chain saturates (C22–C32) increased under atmospheric pressure. Gas Chromatography Mass Spectrometry analyses of aromatics showed that several naphthalene series compounds (naphthalene, C1-naphthalene, and C2-naphthalene) were biodegraded in the sulfate-reducing enrichment under both atmospheric pressure and high pressure. Our study has discerned the linkages between the biodegradation characteristics of crude oil and pressures, which is important for the future application of bioenergy with CCUS (bio-CCUS).